Enhanced antimalarial effects of chloroquine by aqueous Vernonia amygdalina leaf extract in mice infected with chloroquine resistant and sensitive Plasmodium berghei strains - Iwalokun, BA (Makerere Medical School, 2008)
BACKGROUND: The emergence and spread of Plasmodium falciparum with resistance to chloroquine (CQ), the safest and cheapest antimalarial drug coupled with the increasing cost of alternative drugs especially in developing countries have necessitated the need to optimize antimalarial actions of plant extracts and restore chloroquine efficacy. OBJECTIVE: The present study determines the ability of Vernonia amygdalina leaf extract to enhance the prophylactic and therapeutic efficacy of chloroquine against Plasmodium berghei malaria in mice. METHODS: Chloroquine sensitive (P. berghei(S)) and resistant (P.berghei(R)) ANKA clones of Plasmodium berghei maintained by serial passage in mice were used to develop respective experimental rodent malaria models based on intraperitoneal injection of 10(6) parasitize erythrocyte suspension in PBS (pH 7.2) and subsequent development of parasitaemia. These models were then used to investigate the prophylactic enhancement of chloroquine (CQ) at 5 mg/kg via combination with selected doses (31.25, 62.5, 125mg/kbw) of Vernonia amygdalina leaf extracts using a 4-day suppression test. Effect of these combinations on the therapeutic efficacy of CQ at 30mg/kg over 3 days were evaluated. Treatment outcomes including parasite clearance (PCT) and rescrudescent time (RT) were compared with CQ-chlorpheniramine combination. The acute toxicity of the extract-CQ combinations was also determined enzymatically. RESULTS: Prophylatically, chloroquine (5mg/kg) in combination with vernonia extracts achieved a dose-dependent (57.2–72.7%) suppression of parasitaemia due to CQ sensitive and resistant P berghei strains in the experimental animals. Therapeutically, chloroquine (30mg/kg for 3 days) combined with vernonia to dose-dependently shorten the parasite clearance times (2.6–4.4 vs. 4.8 days; P < 0.05 for CQ-V62.5/125 combination), prolong the recrudescent times (8.9–18.9 vs. 7.2 days; P < 0.05) and improve day 14 cure rate (66.7–100 vs. 58.3%) in the treated P. berghei(S) infected mice compared to CQ monotherapy. Whereas CQ monotherapy failed, resolution of parasitaemia due to the CQ resistant parasite with day 14 cure rates of 25 – 100% were also observed with these combinations. In therapeutic terms, the potencies of CQ-V125 combination were comparable to those of CQ-chlorpheniramine (0.25mg/kg, 12hourly, 7 days) in the infected animals. Toxicity testing indicates that these combinations elicited mild to - moderate increases in the liver enzymes measured when administered orally to mice for 7 days. CONCLUSION: This study indicates that Vernonia amygdalina leaf extract dose - dependently restore the efficacy of CQ against CQ resistance P. berghei malaria in mice.